Multimodality imaging spectrum of complications of horseshoe kidney - Shah, Hardik U; Ojili, Vijayanadh (Indian Journal of Radiology and Imaging, 2017)
Horseshoe kidney is the most common congenital renal fusion anomaly with an incidence of 1 in 400–600 individuals. The most common type is fusion at the lower poles seen in greater than 90% of the cases, with the rest depicting fusion at the upper poles, resulting in an inverted horseshoe kidney. Embryologically, there are two theories hypothesizing the genesis of horseshoe kidney – mechanical fusion theory and teratogenic event theory. As an entity, horseshoe kidney is an association of two anatomic anomalies, namely, ectopia and malrotation. It is also associated with other anomalies including vascular, calyceal, and ureteral anomalies. Horseshoe kidney is prone to a number of complications due to its abnormal position as well as due to associated vascular and ureteral anomalies. Complications associated with horseshoe kidney include pelviureteric junction obstruction, renal stones, infection, tumors, and trauma. It can also be associated with abnormalities of cardiovascular, central nervous, musculoskeletal and genitourinary systems, as well as chromosomal abnormalities. Conventional imaging modalities (plain films, intravenous urogram) as well as advanced cross-sectional imaging modalities (ultrasound, computed tomography, and magnetic resonance imaging) play an important role in the evaluation of horseshoe kidney. This article briefly describes the embryology and anatomy of the horseshoe kidney, enumerates appropriate imaging modalities used for its evaluation, and reviews cross-sectional imaging features of associated complications.
Keywords: Complications; horseshoe kidney; multimodality